Implementasi Kebijakan Tentang Penerbitan Surat Persetujuan Berlayar (SPB) Pada Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas II Benoa - I Wayan Sugiarta (STISIP Margarana, 2025)
This study analyzes the implementation of the policy of issuing Sailing Approval Letters (SPB) at the Benoa Class II Port Authority and Kesyahbandaran Office. SPB is a state document issued by syahbandar for ships that have met seaworthiness requirements before sailing. The problems identified include the number of ships sailing without SPB, delays in issuing documents, lack of understanding of fishermen about SPB rules, and the condition of ships that do not meet standards. This violation can be subject to a maximum of 1 year in prison and a fine of IDR 1 billion. The study uses Edward III's implementation theory with four variables: communication, resources, disposition, and bureaucratic structure. The results of the study show that the implementation of the SPB policy has been running well, but there are still obstacles in the form of budget limitations and low awareness of the service user community about the importance of SPB. The recommendations put forward include increased socialization and communication to reduce violations, increased local government budget allocation for law implementation, and increased public awareness through technical guidance and socialization involving relevant stakeholders to ensure sailing safety.